Tri Education Center Synergy: Opportunities and Challenges for the Implementation of 13-Year Compulsory Learning Based on Integrative Holistic Early Childhood Education in Pusakamulya - Iin Sinta; Nita Nurbaeti; Okke Rosmaladewi (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to examine the synergy of the Tri Education Center in the implementation of Integrative Holistic Holistic Early Childhood Education in Pusakamulya Village, as well as identify opportunities, challenges, and development strategies. The research uses a qualitative approach with a case study method to deeply understand the involvement of families, schools, communities, and village governments in supporting PAUD services. The data source consists of primary and secondary data. Primary data was obtained from the head of PAUD, teachers, parents, community leaders, posyandu cadres, and village governments, while secondary data came from the 2025 Indonesian PAUD Profiling document and related policy documents. Data collection techniques are carried out through observation, interviews, and documentation with instruments in the form of observation guidelines, interviews, and documentation sheets. Data analysis was carried out through data reduction, data presentation, and conclusion drawn, while data validity was tested using triangulation of sources and techniques. The results of the study show that the implementation of compulsory learning has opportunities through national policy support, the existence of six PAUD institutions, and cross-sector collaboration. However, challenges still arise in the form of family economic limitations, low public awareness, limited facilities, and weak coordination between education actors. The implications of the research emphasize the importance of strengthening the synergy of the Tri Education Center for equitable access and quality of early childhood education. This research suggests strengthening village policies, increasing socialization to parents, and sustainable collaboration between the education, health, and community sectors.